DESCRIPTION OF THE PSYCHOLOGICAL STATE OF THE CHARACTER MIRYOQUB IN CHOLPON'S NOVEL "NIGHT AND DAY" - Sharipov Maʼmur Mansurovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
"Night and Day"Abdulhamid Sulaiman Cholpon is one of the works that have gained popularity for a long time in the history of Uzbek novels. In the work, the author uses naturalness, sincerity, depth of content, and the method of depicting people's life in a realistic state. The novel artistically describes the life of the Uzbek people at the beginning of the 20th century, and describes problems such as the illiteracy of the population, the lack of rights and freedom of women, the qualities characteristic of the Uzbek people, and the relationships between people. In this work,the position of servants in Uzbek households at the beginning of the 20thcentury is analyzed.